(untitled) (Contemporary Journal of Social Science Review, 2025)
Marxism, serial monogamy and patriarchy intersect as systems of power, where patriarchal web enforce gender roles through monogamous relationships, limiting women’s individuality. In Marxist terms, these relationships mirror capitalist exploitation, with men having authority over both economical resources and social powers, treating women as property or labor to maintain dominance. The present study, titled “Dialectics of Desire: A Marxist Reading of Serial Monogamy in Hurston’s Their Eyes Were Watching God”, explores the odyssey of Janie Crawford against the complex backdrop of the early 20th-century African American experience. This article scrutinizes the complexities of serial monogamy within the narrative through a Marxist lens, exploring how Janie’s three marriages reflect the dialectical tensions between personal desire and social and economic intricacies. Eventually, this study contributes to a subtle understanding of how Hurston’s narrative subverts established presumptions of marriage and financial quest. It also offers critical insights into class struggle and the impact of capitalism on personal relationships during a transformative era.